Synthesis and Characterization of Nitrogen-Doped Activated Carbon for Lithium Battery Anode Applications - Trihutomo, Prihanto; Puspitasari, Poppy; Radja, Muhammad Bustomi; Busono, Milzam Rahmat (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Nitrogen-dopped activated carbon was synthesized to see its effect on the characterization of the nitrogen surface functional groups, crystal size, and morphology of the resulting sample. Synthesis of nitrogen-doped activated carbon was carried out by varying the addition of Urea as a nitrogen doping source. Activated carbon compared its characteristics with variations in the concentration of added Urea to activated carbon, at 1:3 and 1:5. The FTIR results obtained were the presence of functional groups indicating the presence of nitrogen bonds in each sample. The crystallinity results showed that the samples were classified as crystalline and nitrogen doping influenced the size of the crystallinity of each sample. The morphology of nitrogen-doped activated carbon shows differences in the grain size of nitrogen-doped activated carbon. Crystallinity and morphology have been shown to affect battery anode performance. The more crystalline of anode material, the electrochemical properties are better. The smaller the grain size of the sample morphology, the stability of the battery cycle is to be great.